Determination of Planetary Nebulae angular diameters from radio continuum spectral energy distribution modelling. Issue 2 (10th March 2021) - Bojičić, I S; Filipović, M D; Urošević, D; Parker, Q A; Galvin, T J
ABSTRACT: Powerful new, high-resolution, high-sensitivity, multifrequency, wide-field radio surveys such as the Australian Square Kilometre Array Pathfinder (ASKAP) Evolutionary Map of the Universe are emerging. They will offer fresh opportunities to undertake new determinations of useful parameters for various kinds of extended astrophysical phenomena. Here, we consider specific application to angular-size determinations of Planetary Nebulae (PNe) via a new radio continuum spectral energy distribution fitting technique. We show that robust determinations of angular size can be obtained, comparable to the best optical and radio observations but with the potential for consistent application across the population. This includes unresolved and/or heavily obscured PNe that are extremely faint or even non-detectable in the optical.